ETIKA DAN KODE ETIK PESERTA DIDIK DI YAYASAN PENDIDIKAN ISLAM JAME PEKOJAN JALAN PENGUKIRAN IV NO. 37A PEKOJAN, JAKARTA BARAT - Nurhayati, Nurhayati; Ahmad, Pendi; Arifin, Zaki Zainal; Benazir, Dyas Mulyani (Jurnal Pengabdian Sosial, 2021)
ABSTRACT In this era of globalization, students have experienced a moral crisis, including juvenile delinquency that is often encountered such as disrespecting teachers and parents, brawls, drunkenness, gambling, even killing. One of the reasons is the influence of outside culture and the lack of teaching ethics from an early age. Inculcating ethical values if taught from childhood, children will get used to good behavior and will give birth to a good generation according to the noble values of the nation and religion. Teachers sometimes forget to teach morals to students, in class only teach subject matter, meet absenteeism, especially during a pandemic like today, teachers and students only face to face via online, making teaching about morals even more distant, so that there are changes in the social world of education. The method of implementing Community Service activities is dialogue-participatory education by explaining the importance of studying ethics and complying with the code of ethics applied at the Jame Pekojan Islamic Education Foundation. In addition, this activity also involved the educator of the Islamic Education Foundation, Jame Pekojan, Jalan Pengukiran IV No. 37A Pekojan West Jakarta which has been teaching ethics to students. The results of this activity the students were explained about the ethics and code of ethics of students in Islamic education. Besides that, it also raises awareness of students to comply with the code of ethics applied at the Jame Pekojan Islamic Education Foundation, because ethical values should be the main goal in the education system in Indonesia. So that students become moral and ethical. Keywords: Ethics, Code of Ethics, and Students  ABSTRAK Di era globalisasi ini, kalangan pelajar telah mengalami krisis akhlak, diantaranya kenakalan remaja yang sering ditemui seperti tidak menghormati guru dan orang tua, tawuran, mabuk, berjudi, bahkan sampai membunuh. Salah satu penyebabnya adalah adanya pengaruh budaya luar dan kurangnya mengajarkan etika sejak dini. Penanaman nilai etika jika diajarkan sejak masa kanak-kanak, maka anak-anak akan terbiasa untuk bertingkah laku yang baik dan akan melahirkan generasi yang baik sesuai nilai luhur bangsa dan agama Para pengajar terkadang lupa mengajarkan moral kepada peserta didik, dikelas hanya mengajarkan materi pelajaran, memenuhi absen, apalagi pada saat pandemik seperti sekarang ini, pengajar dan peserta didik hanya tatap muka melalui online, membuat pengajaran mengenai moral semakin jauh, sehingga terjadilah perubahan dalam dunia sosial pendidikan. Metode pelaksanaan kegiatan Pengabdian Pada Masyarakat bersifat edukasi dialog-partisipatif dengan cara menerangkan mengenai pentingnya mempelajari etika dan mematuhi kode etik yang diterapkan di Yayasan Pendidikan Islam Jame Pekojan. Selain itu, kegiatan ini juga melibatkan pendidik Yayasan Pendidikan Islam Jame Pekojan Jalan Pengukiran  IV  No.  37A Pekojan  Jakarta  Barat yang selama ini telah mengajarkan etika kepada peserta didik. Hasil kegiatan ini para peserta didik dijelaskan mengenai etika dan kode etik peserta didik dalam pendidikan Islam. Disamping itu juga menumbuhkan kesadaran peserta didik untuk mematuhi kode etik yang diterapkan di Yayasan Pendidikan Islam Jame Pekojan, karena nilai etika sudah seharusnya menjadi tujuan utama dalam sistem pendidikan di Indonesia. Agar peserta didik menjadi bermoral dan beretika.Kata Kunci: Etika, Kode Etik, dan Peserta Didik